(untitled) (The Pakistan Development Review, 2003)
The paper aims to assess the impact of privatisation on employment and output in Pakistan. It uses edible oil and cement sectors as a case study in a pre- and post-privatisation comparative framework. Assessing the impact of privatisation in Pakistan is important at this juncture for two reasons. Firstly, the country is facing a severe economic crisis and privatisation forms an integral part of an array of reform measures recommended by multi-lateral donors as well as policy-makers within and without the country. Burki [(2000), p. 152] observes, “The economy and state of Pakistan are in crisis…. Pakistan has not faced a crisis of this magnitude in its entire 50-year history”. He refers to the five different crises that have combined to create this situation. These are: the global financial crisis, Pakistan’s short-term liquidity problem, economy’s structural weaknesses, severe social backwardness, and, finally, the crisis of governance. Burki (2000) suggests several solutions to the problems, and privatisation is one of the ways to restructure the economy and improve the quality of governance.